Observation of on-ice wind waves under grease ice in the western Arctic Ocean - Kodaira, Tsubasa; Waseda, Takuji; Nose, Takehiko; Sato, Kazutoshi; Inoue, Jun; Voermans, Joey; Babanin, Alexander (Polar Science, 2021)
The significant reduction of the sea ice extent in the western Arctic has been observed by the sustained satellite observations since 1979. The opening ocean is now allowing waves to evolve and propagate under the presence of the Arctic sea ice. A better understanding of the wave-ice interaction is necessary for the safe shipping over the sea ice covered Arctic Ocean and to improve the Arctic climate projection. During R/V Mirai Arctic Expedition in October 2019, two drifting wave-buoys were concurrently deployed in the open ocean and the Arctic marginal ice zone (MIZ) with grease ice and pancake ice. The wave and sea ice conditions at the time of the deployments were documented in detail. Based on the wave buoy data and the sea ice edge estimated by a Synthetic Aperture Radar (SAR) image, attenuation rates of waves under the grease ice are estimated. Good agreement in the frequency dependency of the wave attenuation rate is presented between the observational results and the theoretical prediction from the viscous model of Weber (1987). The agreement implies that the observed surface waves were attenuated by the viscous damping beneath grease ice. It is also found that the observed attenuation rates were generally lower than the previous studies. Several possible factors are discussed, such as the sea ice type, wind energy input, and uncertainties in the estimation of the attenuation rate. journal article